Antidiabetic Activities of Agarwood (Aquilaria malaccensis) Leaf Extracts via Enhanced Insulin Secretion in BRIN-BD11 Pancreatic Beta-Cells - Prayogo, Yanico Hadi; Sari, Rita Kartika; Hamidi, Zikri; Syafii, Wasrin; Harlina, Eva; Prasetyo, Bayu Febram (Jurnal Sylva Lestari, 2025)
Agarwood leaves (Aquilaria malaccensis), a non-timber forest products, shows significant potential as a source of antidiabetic compounds. This study aims to evaluate the antidiabetic activity of agarwood leaves and their cytotoxicity on pancreatic beta-cells, as well as predict their compound bioactivity through an in silico approach. The leaves were extracted using ethanol, water, and a mixture of ethanol–water with the assistance of ultrasound irradiation. The extracts were then tested in vitro for their antidiabetic potential by assessing their ability to inhibit the alpha-glucosidase enzyme and their effect on insulin secretion, as well as their cytotoxicity on BRIN-BD11 pancreatic beta-cells. The phytocompounds in the extract were identified using liquid chromatography-mass spectrometry, and their binding behavior was studied by in silico molecular docking. Among the three, the ethanol–water extract showed the highest extraction yield. Cytotoxicity assays revealed that the ethanol–water extract was cytotoxic at high concentrations (1000 µg/mL), but safe at lower concentrations. The alpha-glucosidase inhibition was relatively weak. Nevertheless, the extracts significantly stimulated insulin secretion in BRIN-BD11 cells up to fivefold compared to untreated cells. In silico studies indicated that xanthone glycoside, flavonoid glycoside, and coumarin compounds exhibit strong binding affinities to multiple insulin-secretion-related proteins. These findings suggest that agarwood leaf extract, particularly ethanol–water extract, possesses promising antidiabetic activity through an insulinotropic mechanism. Keywords: agarwood, alpha-glucosidase, insulinotropic, molecular docking